(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to determine the level of maturity of digitalization in the current supply chains of the Daura refinery, the research sample, which was chosen as one of the oldest and largest Iraqi refineries that supply Baghdad Governorate with petroleum derivatives, which is the highest governorate in terms of population density. The main research problem is summarized in the weakness of supervision and control over operations in the research sample and the failure to fill the local capacity of petroleum derivatives due to the low production capacity resulting from a shortage of digital technologies used in the stages of the refinery supply chain, in addition to the failure of digital technologies in the refinery to keep pace with the technologies used by suppliers, which hinders integration and coordination between suppliers. For all of this, the level of digitalization should be analyzed as a first step to enable the development of a future plan for digital transformation. Therefore, this problem can be summarized in the following question: What is the reality of the level of maturity of digital supply chains in the Daura refinery? The researcher adopted the case study approach for descriptive research due to its suitability to the nature and directions of the current research in gap analysis, using the checklist as the main tool for collecting data. Data analysis was conducted using appropriate mathematical equations such as frequencies, weighted arithmetic mean, percentage, and gap size. The results revealed that the maturity level of the refinery supply chain is at the initial level, i.e., the second level out of five levels.